Physicochemical and Spectroscopic Characterization of Glycogen and Glycogen Phosphorylase b Complexes - Pandora Karakousi; Maria Karayianni; Evangelia D. Chrysina; Stergios Pispas (Polysaccharides)
Glycogen is a natural polysaccharide used as an energy storage macromolecule. The role of glycogen metabolism in type 2 diabetes mellitus has been under investigation for several years, along with its implication in cancer and cardiovascular and neurodegenerative diseases. Previous studies using pig liver glycogen with rabbit muscle glycogen phosphorylase (RMGPb), which catalyzes the first step of glycogen degradation to glucose-1-phosphate, showed that the surface of an average glycogen molecule is covered by a total of 20 RMGPb dimeric molecules. In this work, we selected oyster glycogen (Glyc) to investigate its interaction with RMGPb by employing biophysical techniques. Dynamic, static, and electrophoretic light scattering were used to investigate the solution behaviors and structures of both the Glyc molecule itself and the formed complexes between Glyc and GPb at different mixing ratios. It was established that the interaction between oyster Glyc and RMGPb is similar to that previously reported for pig liver glycogen. Moreover, the structure of the complexed GPb was monitored by fluorescence and FTIR spectroscopy.